Associations between air pollution and cardio-respiratory physiological measures in older adults exercising outdoors. Issue 8 (17th November 2021) - Stieb, David; Shutt, Robin H.; Kauri, Lisa M.; Mason-Renton, Sarah; Chen, Li; Szyszkowicz, Mieczyslaw; Dobbin, Nina A.; Rigden, Marc; Jovic, Branka; Mulholland, Marie; Green, Martin S.; Liu, Ling; et al.
ABSTRACT: We examined whether exercising indoors vs. outdoors reduced the cardio-respiratory effects of outdoor air pollution. Adults ≥55 were randomly assigned to exercise indoors when the Air Quality Health Index was ≥5 and outdoors on other days (intervention group, n = 37), or outdoors everyday (control group, n = 35). Both groups completed cardio-respiratory measurements before and after exercise for up to 10 weeks. Data were analyzed using linear mixed effect regression models. In the control group, an interquartile range increase in fine particulate matter (PM2.5 ) was associated with increases of 1.4% in heart rate (standard error (SE) = 0.7%) and 5.6% (SE = 2.6%) in malondialdehyde, and decreases of 5.6% (SE = 2.5%) to 16.5% (SE = 7.5%) in heart rate variability measures. While the hypothesized benefit of indoor vs. outdoor exercise could not be demonstrated due to an insufficient number of intervention days (n = 2), the study provides evidence of short-term effects of air pollution in older adults. ISRCTN #26552763.